THE EFFECT OF 20% CURCUMA LONGA EXTRACT ON SMEAR LAYER CLEANING IN APICAL THIRD OF THE ROOT CANAL - Arlita Jemima br Surbakti; Martha Mozartha; Merryca Bellinda (Universitas Baiturrahmah, 2022)
Background: Irrigation was aimed to clean the root canal during the mechanical instrumentation process in the endodontic treatment. The ideal root canal irrigant should be able to clean both organic and inorganic smear layers, especially in the apical third region. Turmeric (Curcuma longa) extract is one of the natural ingredients containing active substances as a surfactant, with the ability to clean the smear layer in the root canal. Objective: To determine the effect of 20% C.longa extract on smear layer cleaning in the apical third region of the root canal. Methods: This was in vitro laboratory experimental study with a post-test research design with a control group. The root canals of the teeth were prepared with the crown down technique using ProTaper Universal. The irrigation was as follows: group A using 20% turmeric extract, group B using NaOCl 2.5% followed by 17% EDTA as positive control, and group C with distilled water as negative control. Specimens were cut longitudinally and evaluated using Scanning Electron Microscope (SEM) with 1000x magnification. The observation data were analyzed by Kappa test, followed by Kruskal-wallis test, and post hoc Mann-whitney. Results: There was no significant difference in apical third region cleanliness between the treatment group and the positive control group. However, the treatment group was significantly different from the negative control group. Conclusion: There was an effect of turmeric extract as a root canal irrigant on smear layer cleaning in the apical third region of the root canal.